Hydrophobic and Hydrophilic IOLs in Patients with Uveitis – A Randomised Clinical Trial - Pålsson S; Schuborg C; Sterner B; Andersson Grönlund M; Zetterberg M (Clinical Ophthalmology)
Sara Pålsson,1,2 Claes Schuborg,2,3 Bertil Sterner,1,2 Marita Andersson Grönlund,1,4 Madeleine Zetterberg1,2 1Department of Clinical Neuroscience/Ophthalmology, Institute of Neuroscience and Physiology, Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden; 2Region Västra Götaland, Sahlgrenska University Hospital, Department of Ophthalmology, Mölndal, Sweden; 3Guldhedskliniken, Gothenburg, Sweden; 4Department of Ophthalmology, Faculty of Medicine and Health, Örebro University, Örebro, SwedenCorrespondence: Madeleine Zetterberg, Sahlgrenska University Hospital, Department of Ophthalmology, Mölndal, SE 431 80, Sweden, Tel +46 31 33 43 31 50, Fax +46 31 41 29 04, Email madeleine.zetterberg@vgregion.sePurpose: To compare inflammatory response, visual acuity, and complications of two intraocular lenses (IOLs) in patients with and without uveitis.Setting: Tertiary referral centre at Sahlgrenska University Hospital/Mölndal, Sweden.Design: Prospective randomised controlled trial.Patients and Methods: Patients with and without uveitis eligible for cataract surgery were randomised to receive a hydrophobic or a hydrophilic square-edged intraocular lens (IOL). Patients undergoing bilateral surgery received a hydrophobic IOL in one eye and a hydrophilic in the other. Visual acuity, flare, and central foveal thickness were used as outcome measures.Results: In total, 34 (61%) patients (52 eyes) with uveitis and 22 (39%) non-uveitic patients (38 eyes) were included in the study. Comparable corrected distance visual acuity (CDVA) was seen, regardless of IOL material. Flare, six months postoperatively, for those undergoing bilateral surgery, showed no significant difference between eyes receiving a hydrophilic IOL or a hydrophobic IOL; mean difference was − 3.2 (SD ± 20.7) ph/ms between eyes with uveitis (p = 0.53) and − 0.6 SD ± 7.5 ph/ms between eyes without uveitis (p = 0.77). No significant difference in cystoid macular edema (CME) was seen for uveitic patients receiving a hydrophobic IOL (n = 2; 8.0%) and those receiving a hydrophilic IOL (n = 6; 22.2%; p = 0.25).Conclusion: No significant differences in postoperative inflammatory reaction or rate of CME were seen regardless of using a hydrophobic or a hydrophilic IOL. In general, an improvement in CDVA was seen after cataract surgery with both types of IOLs. Thus, the present study did not support either of the IOL materials as advantageous in patients with uveitis.Plain Language Summary: Uveitis, an inflammatory eye condition, often leads to patients needing cataract surgery. The surgery involves removing the eye’s clouded lens and typically replacing it with an artificial lens known as an intraocular lens. Improvement in vision and possible complications vary depending on the type of replacement lens used. This randomised controlled trial compares inflammation, improvement in vision, and possible complications in patients that received two differing types of intraocular lenses. Improvement in vision was seen in both lens types yet neither lens type was superior in terms of inflammation.Keywords: biocompatibility, cataract, complications, implant, inflammation